Implementation of language development for children in daycare - Halimatus Sakdiah; Delfi Eliza (Institut Agama Islam Negeri Langsa, 2021)
Language development activities in daycare are essential because they can increase children's vocabulary. This study aims to determine how the process of implementing children's language development activities in daycare centres. This study uses the qualitative method. The data were collected by observing the language development of children aged 2-4 years at the Twin Course Daycare and interviewing six caregivers there. The study results showed that the implementation of language development in the Twin Course daycare centre was carried out well. It can be seen from how the teacher applies it in daily activities by reading stories, playing games that can stimulate children's language, listening to the radio, dancing, and responding to children. Therefore, research related to the effective implementation of the language development program can be studied further.